Transcriptome Profile of a Long-Juvenile Soybean Genotype Huaxia-3 Under Short and Long Photoperiod - Enoch Sapey; Bingjun Jiang; Luping Liu; Shan Yuan; Tingting Wu; Seifeldin Elrayah Ibrahim; Shi Sun; Yanlei Yue; Tianfu Han (Plant Molecular Biology Reporter, 2022)
The j allele delays flowering and enhances yield of long juvenile (LJ) soybean under short day (SD) condition. However, the underlying mechanism of j in flowering pathway of soybean is not fully known. The objective of the study is to profile the transcriptome of Huaxia-3 (HX3), a typical long juvenile soybean variety with a loss of function allele ( j ) for the J gene. This helps to identify the genes implicated in delayed flowering in the long juvenile soybean variety and the pathways involved. Phenotypic analysis revealed HX3-delayed flowering and matured later than the transgenic line with the functional J gene under SD. RNA-Seq analysis was conducted to compare the transcriptome of HX3 relative to the one overexpressing J gene under SD and long day (LD). A total of 674,800,494 clean reads were generated, of which 626,517,161 (93%) were uniquely mapped to the soybean reference genome. A total of 31 and 2311 genes were differentially expressed in the HX3 under SD and LD conditions respectively. The circadian rhythm pathway was the most significantly enriched pathway in the HX3 under SD condition. The GmELF3a ( Glyma.04G050200 ) and FLOWERING LOCUS T ( FT ) genes such as GmFT2a ( Glyma.16G150700 ) and GmFT5a ( Glyma.16G044100 ) were downregulated, whiles GmFT4 ( Glyma.08G363100 ) was upregulated in the HX3 under SD. Under LD FT homologs, GmFT4 ( Glyma.08G363100 ) was downregulated and GmFT1a ( Glyma.18G299000 ) was upregulated. Our study suggests that these FT homologs may be involved in delayed flowering of LJ soybean under SD.